Kontaminan Pangan (Mikroba, Kimia, Fisik) dan Risiko Kesehatan di Lingkungan Pendidikan Kuliner - Amalia Akita; Roni Gunawan; Herkules Herkules (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Background: Food safety in culinary education institutions is not yet fully a major concern, even though the practice kitchen is a space that is vulnerable to contamination. This study analyzed three main types of microbiological, chemical, and physical contaminants and their impact on health in the culinary vocational education environment. Method: The method used is in the form of a literature review from various national and international scientific sources published in 2015–2025. Result:The results of the analysis show that the three types of contamination are interrelated and often root from human behavior, limited facilities, and weak application of sanitation and hygiene principles. Students have generally accepted basic theories of food safety, but are still lacking in practical applications such as temperature control, cross-contamination prevention, and chemical and physical hazard identification. Conclussion : Risk awareness also tends to be low, especially when handling raw materials or using shared equipment. Therefore, a real-world practice-based learning approach and risk assessment need to be applied consistently. The integration of educational models such as risk-based hygiene training and Green and Safe Kitchen can shape hygienic behavior, professional ethics, and social responsibility of students as prospective workers in the food service industry.